Lead Acid Battery Analysis Using S-Transform - Selamat, Nur Asmiza; Mohamad Basir, Muhammad Sufyan Safwan; Abdullah, Abdul Rahim; Musa, Haslinda; Ranom, Rahifa (Insight Society, 2017)
This paper proposes a new signal processing technique using time-frequency distribution (TFD),namely S-ransform (ST)for battery parameters estimation.Compared to other TFDs such as short time Fourier transform (STFT) and wavelet transform (WT),ST technique offers more promising results in a low frequency application analysis, especially battery.The results of the ST are the parameters of instantaneous means square voltage (VRMS (t)),instantaneous direct current voltage (VDC (t)) and instantaneous alternating current voltage (VAC (t)) extracted from the time-frequency representation (TFR). Simulation through MATLAB has been conducted using equivalent circuit model (ECM),using 12 V lead acid (LA) battery with capacities from 1.0 Ah to 10.0 Ah.For the battery model,charging/discharging signal has been used to estimate the battery parameters from the ST technique to determine battery characteristics.From the signal characteristics of battery capacity versus VAC (t) obtained,new equation is proposed based on the curve fitting tool.The advantage of this technique embraces a better capability in estimating battery parameters at low frequency component,resulting in better frequency and time resolutions compared to previous TFDs.